Analysis of health service waste management in a public hospital in the municipality of Paragominas (Research, Society and Development, 2020)
Waste from health services is proven to be harmful to the environment and human health. Thus, the handling of this type of waste must be carried out in order to minimize the risks and must be carried out in accordance with the laws in force. Therefore, this study aimed to analyze the management of Health Service Residues in a public hospital in the municipality of Paragominas/PA. To this end, the methodology developed used three stages: (1) the application of instruments for data collection; (2) tabulation of data and statistical analysis and (3) assessment of the compliance of RSS management in the municipal hospital of Paragominas and with the legal requirements. The results obtained in the survey showed that 47% of employees have not yet received any type of training to handle RSS and 13% have not been instructed to use personal protective equipment, as a result, 33% of employees have stopped using protective equipment. at least once during the handling of RSS; in addition to several non-conformities in the hospital with the legislation regarding the management of RSS, these being identified in the stages of segregation, packaging, collection and external transportation, waste shelter and Management Plan.